Chemical fingerprinting and antioxidant properties of Glochidion philippicum - Khairuddin, Khairuddin; Manggau, Marianti A.; Rante, Herlina; Hardiyanti, Widya; Latada, Nadila P.; Umar, Abdul H.; Nur, Syamsu; Wahyudin, Elly; Rahman, Latifah; Yulianty, Risfah; Nainu, Firzan (Narra Sains Indonesia, 2025)
Glochidion philippicum has been suggested to exhibit considerable pharmacological potential, yet its chemical composition and bioactivity remain inadequately explored. The aim of this study was to investigate the chemical fingerprint and antioxidant properties of G. philippicum leaf extracts using Fourier-transform infrared spectroscopy (FTIR) with chemometric analyses, and in vitro and in vivo evaluations. Four extraction methods (maceration, reflux, ultrasound-assisted extraction (UAE), and microwave-assisted extraction (MAE)) were optimized with water, 70% ethanol, ethyl acetate, and n-hexane as solvents. FTIR profiles were analyzed with principal component analysis (PCA), hierarchical cluster analysis, and orthogonal partial least squares discriminant analysis. An in vitro study assessing the free radical scavenging capacity was conducted using the 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and ferric-reducing antioxidant power (FRAP) methods, while in vivo evaluations were conducted using Drosophila melanogaster to measure antioxidant enzyme activity and expression of endogenous antioxidant-related genes. FTIR profiles identified functional groups contributing to antioxidant activity. In vitro assays using ABTS and FRAP methods revealed that extracts obtained with 70% ethanol and water exhibited the highest antioxidant activity, attributed to key functional groups such as C=C (aromatic), O−H (acidic), N=O (nitro), and C−O (ester). In vivo studies showed that ethanol-based MAE extracts (MAEEO) significantly improved the survival of autoinflammatory PGRP-LBΔ mutant larvae exposed to heat-killed Escherichia coli. Real-time quantitative PCR analysis indicated this effect was dependent on endogenous antioxidant gene activation. The study highlights that G. philippicum leaf extracts as a natural source of bioactive compounds with exogenous antioxidant properties, offering potential for therapeutic applications.